Non-destructive testing :proceedings of the 4th European conference, London, UK, 13-17 September 1987 /edited by J.M. Farley and R.W. Nichols. - Farley, J. M.
Proceedings of the 4th European Conference on Non-destructive Testing, and of the 16th EWGAE Conference held in conjunction with the above.